TAWAKAL: Konsep Intern Control dalam Bisnis Syariah - Yohan Bakhtiar (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2021)
The concept of intern control has not been widely developed by researchers in the accounting/auditing field. This study aims to uncover the meanings of intern control in Islamic business perspective. Islamic phenomenology used as a method of this research. The concept of intern control with Tawakal principle is the substance of the findings in this study. Tawakal means fully surrendering to Allah SWT in facing or waiting for the results of a job, or waiting for the consequences of a situation.